Corrosion of limestone tablets in sulfidic ground-water: measurements and speleogenetic implications - Galdenzi Sandro (International Journal of Speleology, 2012)
The measurement of the weight loss in limestone tablets placed in the Grotta del Fiume (Frasassi, Italy) provided data on the rate of limestone dissolution due to the sulfidic water and on the influence of local environmental conditions.A linear average corrosion rate of 24 mm ka-1 was measured in stagnant water, while the values were higher (68-119 mm ka-1) where the hydrologic conditions facilitate water movement and gas exchanges. In these zones the increase in water aggressivity is due to mixing with descending, O2-rich, seepage water and is also favored by easier gas exchange between ground-water and the cave atmosphere. Very intense corrosion was due to weakly turbulent flow, which caused evident changes in the tablets shape in few months. A comparison between the measured corrosion rates and the cave features showed that the values measured in the pools with stagnant water are too low to account for the largest solutional cave development, while the average values measured in the zones with moving water are compatible with the dimension of the cave rooms in the main cave levels, that must have developed when the base level was stable and hydrologic conditions favored the increase of water aggressivity.